Microsoft C run-time library - Jamsa, Kris A. ([S.l.] : Microsoft Pr, 1989)
This reference provides instant access to concise information on the most commonly used functions and macros in the Microsoft C and Microsoft QuickC Run-Time Library. It includes information on syntax, calling sequences and variables and working examples along with notes and comments.